A NARRATIVE REVIEW OF PUERARIA LOBATA'S EFFICACY IN LUNG CANCER MANAGEMENT - Uday Kumar Panigrahi, Megha Jha (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Lung cancer, a significant cause of cancer-related deaths globally, primarily attributed to smoking, remains a major public health concern. This article delves into the potential of Pueraria lobata, commonly known as kudzu, in managing lung cancer. Beginning with an overview of lung cancer prevalence, types, and treatment challenges, the article transitions into discussing kudzu's traditional medicinal uses, emphasizing its historical significance in Chinese medicine. Notably, puerarin, a key compound in kudzu, has exhibited anticancer properties in various studies, including inhibition of cell proliferation and induction of apoptosis. The article further explores the pharmacological properties of kudzu, its chemical composition, and mechanisms of action relevant to lung cancer treatment, elucidating its potential as a chemotherapeutic agent. Preclinical studies, both in vitro and in vivo, demonstrate promising results in inhibiting tumor growth and inducing cell death. Clinical evidence, although limited, suggests the efficacy of kudzu-based treatments in managing lung cancer, with some cases showcasing improvement in symptoms and disease progression. However, safety considerations and adverse effects must be carefully evaluated, especially in individuals with specific medical conditions or those taking certain medications. Overall, the aim of this article is to review the existing literature on Pueraria lobata's efficacy in lung cancer management, shedding light on its potential as a complementary or alternative therapeutic approach in combating this deadly disease.